Commercial Car Sharing, Complaints and Coping: Does Sharing Need Willingness?. Issue 4 (2nd October 2018) - Kent, Jennifer L.; Dowling, Robyn
ABSTRACT: Commercial car sharing is arguably one of the more positive shared transport innovations of the past decade, with evidence suggesting that car sharing reduces rates of car ownership, frequency of car use and vehicle kilometres travelled. In this paper, we propose that transitions to successful sharing practices are dependent on those 'doing' transition maintaining a positive attitude towards the alternative practice. We call this willingness. Drawing on qualitative, empirical data from car sharers in Sydney, Australia, we use three themes to explain why willingness is central to mobility transitions. Without it, new ways of sharing will struggle to gain traction.